A Trauma Reading of Isaiah 1–12 from the “Unity Movement” Perspective : Festschrift for GTM Prinsloo - Groenewald, Alphonso; Esterhuizen, Elizabeth (Journal for Semitics, 2023)
In this contribution we focus firstly on the “unity movement” which has changed the face of Isaianic studies over the last 30 or more years, having been characterised by the Duhmian interpretation of three separate books for nearly 100 years. The unity movement focusses on the book of Isaiah as a literary unity, but it does not deny the historical growth of this literary masterpiece which took place over centuries. Secondly, we give a brief overview of the use of trauma theory as a reading lens in biblical studies and its implication for reading the book of Isaiah in this manner. In the third part we focus on three themes which are important from the perspective of the unity of the book of Isaiah (specifically in Isaiah 1–12 which is the first major subsection within the larger composition of the book of Isaiah). These three themes are important for a trauma reading of the book of Isaiah, as will be indicated in this contribution: the concept of the we-group (remnant), the woe oracles, and the theme of the “day of YHWH // this day.” These themes are briefly dealt with within Isaiah 1–12, although they have major implications for a more detailed study of the book of Isaiah (read as a literary unity) from a trauma theoretical perspective.